Review of research and application of evaporative cooling in preservation of fresh agricultural produce - Ndukwu, M. C.; Manuwa, S. I. (International Journal of Agricultural and Biological Engineering, 2014)
Extensive review of evaporative coolers for the preservation of fresh agricultural produce in some countries was presented. Most of the designs employ mainly direct evaporative cooling methods which are simple but with lower thermal performance, and can only be used for short term storage of agricultural produce with moderate respiratory rates. Researches into novel technologies in evaporative cooling systems which can improve the cooling performances, such as membrane air treatments, dew point type and heat pipe type heat exchanger in indirect/direct evaporative cooling application, and their feasibilities in agricultural storage are either absent or scarce. Some kinds of materials especially agricultural residues have been used for air water contact in evaporative cooling in different climates, but most of the analyses focused on effect of air flow rate and pad thickness on the cooling effectiveness, and the energy efficiency and evaporation loss of these materials in most cases were not evaluated or presented. The paper highlights the prospects and constraints of commercialization and marketing of evaporative coolers in some developing countries, and the general weakness in researches and the ways forward in new area of research and development are concluded. Keywords: agricultural products, evaporative cooling, passive coolers, active coolers, pad materials DOI: 10.3965/j.ijabe.20140705.010 Citation: Ndukwu M C, Manuwa S I. Review of research and application of evaporative cooling in preservation of fresh agricultural produce. Int J Agric & Biol Eng, 2014; 7(5): 85－102.